Sustainable High-Rise Buildings: Design, technology, and innovation - Al-Kodmany, Kheir; Du, Peng; Ali, Mir M (IET built environment series, 2022)
The rapid increase in urban population, land prices and land preservation, urban regeneration, as well as globalization and climate change have been forcing cities to build upward. High-rises can be part of a more sustainable solution if the construction and engineering challenges are addressed before construction starts. Smart technologies are being integrated in the digital environment to allow for better energy efficiency, safety and security, and to maximize the health and well-being of the occupants. Delivered by a team of world leading experts, this comprehensive edited book covers the state-of-the-art of advanced research, innovations, and future perspectives towards sustainable high-rise buildings. The book is structured in three parts from architecture to engineering and city planning including sustainable environmental systems, skybridges, curtain walling resiliency, tall timber buildings, sustainable structural engineering, core design and space efficiency. It also includes seismic design, mass-damping-based approaches, innovative bio-polymeric agro-based materials, high-rises versus sprawl, transit-oriented development, mobility and urban space networks, resilience thinking, and interdependence of tall buildings and the city. Architects, engineers, researchers, energy and facility managers, urban designers, project planners and developers, and smart building solutions experts as well as faculty members, postdocs, advanced students who are working in the fields of the built environment, building construction, system design, civil engineering, architecture, urban planning, smart cities, sustainability and resiliency and environmental engineering, and who are exploring sustainable building practices, will find this new advanced reference most useful and inspiring.